Is Kugel Herniorraphy Really Minimally Invasive?: A Prospective, Randomized Study (Annals of Medical Research, 2021)
Background: Kugel herniorraphy had been advocated as a minimally invasive technique. The purpose of this study was to compare inflammatory responses and clinical outcomes after Kugel and Lichtenstein procedures.Patients and methods: Thirty patients with unilateral inguinal hernia were randomized into Kugel and Lichtenstein repair groups. Peripheral venous blood samples were collected, to measure the levels of interleukin-6 and C-reactive protein, just prior to surgery and then 12 and 48 hours postoperatively. Postoperative acute and chronic pains were evaluated. Time to return normal activities and work was recorded.Results: Interleukin-6 levels significantly increased after Lichtenstein procedure. C-reactive protein levels were significantly increased in both groups. Patients had less postoperative pain and they recovered earlier after the Kugel procedure.Conclusions:In conclusion our data show that Kugel herniorraphy causes less inflammatory response, less postoperative acute pain and rapid recovery compared with Lichtenstein technique.
Keywords: Kugel herniorraphy, Lichtenstein procedure, Inflammatory response, Minimally invasive